2013
DOI: 10.1002/cssc.201300436
|View full text |Cite
|
Sign up to set email alerts
|

Direct Gas–Solid Carbonation Kinetics of Steel Slag and the Contribution to In situ Sequestration of Flue Gas CO2 in Steel‐Making Plants

Abstract: Direct gas-solid carbonation of steel slag under various operational conditions was investigated to determine the sequestration of the flue gas CO2 . X-ray diffraction analysis of steel slag revealed the existence of portlandite, which provided a maximum theoretical CO2 sequestration potential of 159.4 kg CO 2 tslag (-1) as calculated by the reference intensity ratio method. The carbonation reaction occurred through a fast kinetically controlled stage with an activation energy of 21.29 kJ mol(-1) , followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(22 citation statements)
references
References 39 publications
0
20
2
Order By: Relevance
“…38 The activation energy determined in this study was slightly lower than those reported by Tian et al, 36 which was 21.29 kJ mol À1 and slightly higher than those reported by Sun et al, 37 which was 14.84 kJ mol À1 for the kinetically controlled stage. 38 The activation energy determined in this study was slightly lower than those reported by Tian et al, 36 which was 21.29 kJ mol À1 and slightly higher than those reported by Sun et al, 37 which was 14.84 kJ mol À1 for the kinetically controlled stage.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…38 The activation energy determined in this study was slightly lower than those reported by Tian et al, 36 which was 21.29 kJ mol À1 and slightly higher than those reported by Sun et al, 37 which was 14.84 kJ mol À1 for the kinetically controlled stage. 38 The activation energy determined in this study was slightly lower than those reported by Tian et al, 36 which was 21.29 kJ mol À1 and slightly higher than those reported by Sun et al, 37 which was 14.84 kJ mol À1 for the kinetically controlled stage.…”
Section: Resultscontrasting
confidence: 65%
“…ln[(1 À h) À2/3 À 1] and ln t in Fig. 36 The rate constant k 1 could be derived and was showed in Table 5. While, ln[1 À 2h/3 À (1 À h) 2/3 ] and ln t in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, use of CO 2 from flue gases could improve environmental performance (Tian et al. ). With respect to alkali activation, the production of alkaline activators is a major environmental drawback.…”
Section: The Environmental Impact Of Stainless Steel Bricksmentioning
confidence: 99%
“…To increase the total CO 2 capture capacity of steel slag, the use of steel slag as the calcium precursor to prepare CaO‐based sorbents for use in the calcium looping process (CLP) has recently been studied , . The CLP relies on the use of a regenerable CaO‐based sorbent for CO 2 capture during cyclic carbonation and calcination reactions .…”
Section: Introductionmentioning
confidence: 99%